2010
DOI: 10.1038/ijo.2010.131
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index, weight change and risk of stroke and stroke subtypes: the Japan Public Health Center-based prospective (JPHC) study

Abstract: Objective: The Japan Public Health Center-based prospective Study examined the association of body mass index (BMI) and weight change with incident stroke in Japanese individuals, for whom BMI levels are generally low. Methods: We used initial data from 1990 to 1994 and 5-year follow-up surveys from 1995 to 1999. We calculated weight change over a 5-year period for 32 847 men and 38 875 women, aged 45-74 years, with no history of cardiovascular disease or cancer. Subjects were followed from the 1995-1999 surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 21 publications
1
33
4
Order By: Relevance
“…The Hisayama study reported that high BMI was associated with a high incidence of cerebral infarction in men, but not in women 25 . The Japan Public Health Center-Based Prospective (JPHC) Study reported that higher BMI was associated with an increased risk of stroke in women, but not in men 23 . Females in the Hisayama study were more likely to be current smokers than those in our study.…”
Section: Discussioncontrasting
confidence: 44%
“…The Hisayama study reported that high BMI was associated with a high incidence of cerebral infarction in men, but not in women 25 . The Japan Public Health Center-Based Prospective (JPHC) Study reported that higher BMI was associated with an increased risk of stroke in women, but not in men 23 . Females in the Hisayama study were more likely to be current smokers than those in our study.…”
Section: Discussioncontrasting
confidence: 44%
“…Studies have revealed a graded association between BMI and stroke risk; the risk of total stroke or IS rises linearly with increasing BMI and in a stepwise fashion for higher BMI categories. [297][298][299] Obesity affects stroke risk in both men and women, even after adjustment for factors such as age, physical activity, smoking, alcohol consumption, and comorbid conditions such as hypertension and diabetes mellitus [297][298][299][300][301][302][303][304][305][306][307] (Table 10). There is no clear evidence that obesity has a stronger impact on stroke risk in women than in men (Table 10).…”
Section: Association Between Obesity and Abdominal Adiposity And Stromentioning
confidence: 99%
“…4 Considering the results of the present study as well as previous studies, the effect of obesity or weight gain on death appears to be considerably smaller in Japanese than Caucasian subjects. In contrast, recent large Japanese prospective studies demonstrated that overweight or obesity assessed using BMI raised the risk of incident stroke only in women, 5 and that of incident coronary heart disease only in men. 17 Another meta-analysis in Japan also found that increased BMI was associated with a higher risk of incident stroke in both men and women, but a higher risk of coronary heart disease only in men.…”
Section: Discussionmentioning
confidence: 87%